Pengaruh Citra Merek, Kualitas Produk, dan Harga Terhadap Minat Beli Konsumen Wizzmie Kota Makassar - Sahabuddin, Romansyah; Arif, Hery Maulana; Dg Manai, Sulfadillah; Suryani, Dila; Sabirin, Aulia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
The purpose of this writing is (1) to find out whether Wizzmie consumers in the city of Makassar are partially influenced by brand image; (2) whether Wizzmie consumers in Makassar city are partially influenced by product quality; (3) whether Wizzmie consumers in Makassar city are partly influenced by price; (4) how much consumers' perceptions of the Wizzmie brand, product quality and price influence their willingness to buy the brand. Forty participants completed the survey for this investigation. This research uses multiple linear regression analysis, quantitative descriptive techniques. Based on the research results, (1) there is no relationship between brand image and customer shopping behavior (p = 0.734 0.05). There is no correlation between product quality and consumer purchasing intentions as shown in (2). At the 0.05 level of significance, the correlation between price and customer behavior is moderate. At the four-decimal level of statistical significance (0.000 0.05), there is a correlation between consumer purchasing behavior and elements such as brand perception, product quality, and cost.